Optimalisasi Potensi Wisata Desa Pintu Angin dan Bonou, Kecamatan Talawi, Kabupaten Sawalunto Melalui Identifikasi Oleh Mahasiswa KKN UNP Untuk Menarik Minat Wisatawan - Yanti, Imelda; Yunita, Nurma; Viona, Rina; Andreza, Netania; Amalia, Nadya; Rahman, Habib Fatur; Eldiansyah, Rofy; Rahmatullah, Figo; Yunita, Sandra; Rahmad, Santika Maretha; Fernanda, Septia Dina; Putri, Rhere Indrya (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
Tumpuk Tangah Village is one of the villages located in Talawi District, Sawahlunto City, West Sumatra. In this village, there are still difficulties in attracting potential tourists who want to travel to Tumpuk Tengah Village, especially in Pintu Angin and Bonou Hamlets, this is the main problem. If the process is not effective, the Hamlet will have difficulty in finding the right Tourism Potential to be needed and developed. The lack of development and training programs can lead to a lack of skills and knowledge among the Community. This can affect them and their ability to deal with the changes that occur. Communities that are not motivated or not fully involved in tourism development can reduce the attractiveness of visiting tourists. One way is the KKN UNP student activity in Talawi Tumpuk Tangah Village, namely identifying Tourism which aims to optimize the village into a Tourist Destination, this program focuses on increasing further Development especially in Pintu Angin and Bonou Villages. we hope that this identification and assessment can be the basis for further development, attracting tourists, and providing economic benefits for the people of Pintu Angin and Bonou Hamlets